O corpo próprio como princípio educativo a partir da perspectiva fenomenológica de Merleau-Ponty - Santos, Luiz Anselmo Menezes (2012)
This work is based on phenomenological perspective of Merleau-Ponty, to substantiate the evidence of an interrelation between the under construction, culture, and the subject of perception, pointing, thus, the evidence of an educational foundation designed to put the body in harmony with the notion of subjectivity. The goal is to defend the idea of the body itself as educational principle, intending to establish a study about how the body makes us essentially beings of relationship with the world and with each other. We thought enlightenment, to identify elements of a design designers of physical education from the relationship between the intellect, morality and the physical body. The intention was to conduct a mapping of thinking education body in the 18th century, through the analysis of pedagogical conceptions of Locke, Rousseau and Kant, seeking to prove the idea of body educated and therefore prepared for the autonomy and morality. The intention was to conduct a mapping of thinking education body in the 18th century, through the analysis of pedagogical conceptions of Locke, Rousseau and Kant, seeking to prove the idea of body educated and therefore prepared for the autonomy and morality. The need to educate the body was adopted in the scenario of modern pedagogy, and despite advances brought by this project, as regards the revaluation of the body under educational, we find the proposal for a body instrument. On the philosophical perspective of Merleau-Ponty, the body is not a thing nor an abstract idea, it is sensitive and intentional presence, which makes the subject a perceptual consciousness incarnated in the world, capable of reaprendê him constantly. This process, however, is not spontaneous; It requires learning and training, since the provisions do not sprout from a metaphysical basis. This body subject, which manifests itself through its drive, displays appropriate codes and beliefs that were due to a particular cultural pattern produced and inherited by perceived context. The body that Merleau-Ponty presents us with is the one we experienced while conducting our intentions, desires and projects. In this sense, we realized the body itself as a principle that enables us to relearn the world. It is in this sense, that the pedagogical practice needs to be guided by a principle of education, we encourage to meditate and reflect on the consequences of the facts, of own shares, and feel.